Synthesis and Characterization of Transition-Metal Complexes of 2-prop-2-en-1-yl-N-hydroxyprop-2-ene-1-sulfinimidothioate Oxime - Tekade, Mayur Sanjay; M. Patil, Pallavi (Journal of Neonatal Surgery, 2025)
In order to examine their coordination behaviour and physicochemical characteristics, a number of transition-metal chelates of 2-prop-2-en-1-yl-N-hydroxyprop-2-ene-1-sulfinimidothioate oxime were created and described. The ligand was synthesized and subsequently interacted with metal salts under regulated pH, temperature, and reflux conditions. With yields ranging from moderate to good (51–58%), representative complexes, such as CdL1 and CuL1, were produced as colourful crystalline solids. Successful complexation was confirmed by clear optical changes, as the copper complex (CuL1) formed an orange solid (58% yield) while the cadmium chelate (CdL1) appeared as a reddish-brown solid (51% yield). The syntheses were optimized by keeping slightly acidic to neutral pH (5.5–6.5) using dilute ammonia and by employing methanol as the reaction medium under continuous stirring and controlled heating. FT-IR, UV-Vis spectroscopy, CHNS elemental analysis, ICP-MS metal estimation, mass spectrometry, NMR spectroscopy, TGA, and X-ray diffraction were used to thoroughly characterize each metal chelate. The analytical results verified the hypothesized molecular formulae and stoichiometries (e.g., C₁₂H₂₀CuN₂O₂S₄³⁻ for CuL1 and C₁₂H₂₀CdN₂O₂S₄²⁻ for CdL1) and indicated coordination through oxime and sulfinimidothioate functional groups. Thermal and spectroscopic studies further demonstrated complex stability and ligand–metal interactions. This study presents a systematic approach for synthesizing and analysing sulphur–nitrogen donor chelating ligands and their metal complexes, contributing to the knowledge of their structural and possible functional uses.